Clinical iron deficiency disturbs normal human responses to hypoxia - Frise, M; Cheng, H; Nickol, A; Curtis, M; Pollard, K; Roberts, D; Ratcliffe, P; Dorrington, K; Robbins, P (American Society for Clinical Investigation, 2016)
Background Iron bioavailability has been identified as a factor influencing cellular hypoxia sensing, putatively via an action on the hypoxia-inducible factor (HIF) pathway. We therefore hypothesised that clinical iron deficiency would disturb integrated human responses to hypoxia. Methods We performed a prospective, controlled, observational study of the effects of iron status on hypoxic pulmonary hypertension. Individuals with absolute iron deficiency (ID), and an iron-replete (IR) control group, were exposed to two six-hour periods of isocapnic hypoxia. The second exposure was preceded by intravenous infusion of iron. Pulmonary artery systolic pressure (PASP) was serially assessed with Doppler echocardiography. Results Thirteen ID individuals completed the study and were age- and sex-matched with controls. PASP did not differ by group or study day prior to each hypoxic exposure. During the first six-hour hypoxic exposure, the rise in PASP was 6.2 mmHg greater in the ID group (absolute rises 16.1 and 10.7 mmHg, respectively; 95% CI for difference, 2.7 to 9.7 mmHg, P = 0.001). Intravenous iron attenuated the PASP rise in both groups, but the effect was greater in ID participants (absolute reductions 11.1 and 6.8 mmHg, respectively; 95% CI for difference in change, -8.3 to -0.3 mmHg, P = 0.035). Serum erythropoietin responses to hypoxia also differed between groups. Conclusions Clinical iron deficiency disturbs normal responses to hypoxia, as evidenced by exaggerated hypoxic pulmonary hypertension that is reversed by subsequent iron administration. Disturbed hypoxia sensing and signalling provides a mechanism through which iron deficiency may be detrimental to human health.